The Tourism Destination Determinant Quality Factor from Stakeholders Perspective - I Gusti Bagus Rai Utama; Christimulia Purnama Trimurti; Ni Made Diana Erfiani; Ni Putu Dyah Krismawintari; Dermawan Waruwu (Lasigo Akademia Indonesia, 2021)
High-quality tourism destinations nowadays become the expectations of tourism stakeholders. However, these quality tourism destinations do not have a definition and key performance indicator that can be used as a measurement indicator, so this research is necessary. This study tries to measure the quality of tourism destinations based on the perspective of Bali tourism respondents. In this survey, the attitude of the respondents was measured using a choice of 5 Likert scales that directly asked their attitude towards various indicators on two elements, namely the tourist quality variable and the destination quality measurement variable. The results of a survey of 200 informants illustrate that the respondents' views on all indicators that are considered as indicators of measuring the quality of tourists and indicators of tourism destinations. They can be used as indicators to measure other destinations with adjustments according to their conditions. The novelty in this studies is three factors that have been formed key factors of tourism destination quality. The first is named the quality beautiful destination and unique attraction. The second factor is named quality tourist spending and respect local culture minded. The third factor is named the quality climate and weather condition and infrastructure.